Perancangan UI/UX Aplikasi Kesehatan Mental “MindEase” Berbasis Mobile dengan Metode Design Thinking - Pande Komang Bhargo Anantha Yogiswara; I Gusti Ngurah Anom Cahyadi Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
The rising global concern over mental health disorders necessitates accessible and quality mental health services. In Indonesia, where 6.1% of the population aged 15 and above experience such disorders, addressing the increasing prevalence becomes imperative. However, barriers like resource scarcity, limited geographic access, and social stigma hinder individuals from accessing professional help. More than 80% of affected individuals lack access to quality, affordable mental health services. In response, the mobile application